2017
DOI: 10.1631/jzus.b1700129
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin KIF4A is associated with chemotherapeutic drug resistance by regulating intracellular trafficking of lung resistance-related protein

Abstract: Multidrug resistance (MDR) is the major impediment to cancer chemotherapy. The expression of lung resistance-related protein (LRP), a non-ATP-binding cassette (ABC) transporter, is high in tumor cells, resulting in their resistance to a variety of cytotoxic drugs. However, the function of LRP in tumor drug resistance is not yet explicit. Our previous studies had shown that Kinesin KIF4A was overexpressed in cisplatin (DDP)-resistant human lung adenocarcinoma cells (A549/DDP cells) compared with A549 cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…KIF4A, a microtubule‐based motor protein, produces directional motion along microtubules. It was reported that KIF4A promoted drug resistance in LUAD (Pan, Zhang, Zhu, & Dong, ) and its high expression was associated with the development of lung cancer (Zhang et al, ). High expression of DLGAP5 and ECT2 was also associated with tumor metastasis and led to poor NSCLC patient prognosis (Q. Wang, Chen, Feng, Zhang, & Wang, ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…KIF4A, a microtubule‐based motor protein, produces directional motion along microtubules. It was reported that KIF4A promoted drug resistance in LUAD (Pan, Zhang, Zhu, & Dong, ) and its high expression was associated with the development of lung cancer (Zhang et al, ). High expression of DLGAP5 and ECT2 was also associated with tumor metastasis and led to poor NSCLC patient prognosis (Q. Wang, Chen, Feng, Zhang, & Wang, ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…KIF4A functioned at a broad range, a recent research also indicated the role of KIF4A in DNA damage response [ 25 ]. In recent years, KIF4A has been shown to play a catalytic role in a variety of cancers [ 3 5 , 12 , 26 32 ]. For example, KIF4A promoted the proliferation of lung cancer cells by forming a complex with PHF14 and activation of KIF4A might be a prognostic biomarker and therapeutic target for lung cancer [ 5 , 26 ], and KIF4A was closely related to the recurrence of liver cancer in hepatocellular carcinoma [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kinesin superfamily 4A (KIF4A) had recently been found to play a role in a variety of tumors including lung and hepatocellular carcinoma and was proved to be closely related to tumor metastasis, recurrence, and many other clinical features associated with poor prognosis [ 3 5 ]. KIF4A had previously been shown to be highly expressed in PDAC [ 6 ]; however, the mechanism of KIF4A in tumor development remained unclear and worth discussing.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that KIF4A is abnormally expressed and negative correlation with poor prognosis in several types of cancer 12–16 . Downregulation of KIF4A could enhance the sensitivity to chemotherapy in some cancers, such as non‐small‐cell lung cancer and prostate cancer, 17,18 which suggest that KIF4A may be a promising therapeutic target for cancers. Although a recent study showed that KIF4A in ESCC is associated with a poor prognosis 19 .…”
Section: Introductionmentioning
confidence: 99%